Performance Verification of Bayesian Network–Based Security Risk Management and Control System for Power Trading Institutions - Kong, Shuqin; Tian, Lin; Sheng, Jiansheng; Lu, En; Luo, Jingqing; Xu, Yun (Frontiers in Energy Research, 2022)
In order to reduce the risk of power trading projects, a security risk management and control system of power trading institutions based on Bayesian network is designed. Establish the overall architecture of risk management and control system, which includes malicious network behavior detection module, controller selection module, data transmission module and management and control result visualization module, and analyze the working principle and function of each module; Based on the hardware design of the system, the regression analysis method is used to evaluate the risk of power transaction, predict the market fluctuation and obtain the risk prediction results; The relationship between security risks and risk influencing factors is analyzed through Bayesian network, the initial list of risks is established, the uncertain risk factors are reasoned, and the security risk management and control model of power trading institutions is established to achieve the goal of risk management and control. The experimental results show that the risk management and control efficiency of this method is high, can realize the comprehensive identification of risk, reduce the loss of power enterprises, and has practical application value.